Arcana of resistance: underground traces of surrealism in O Físico Prodigioso, by Jorge de Sena - Sarmento-Pantoja, Tânia (Revista de Letras, 2010)
This paper aims to present an analysis of O Físico Prodigioso by Jorge de Sena considering in particular aspects related to the symbolism of the Tarot. Keywords: Jorge de Sena. Esotericism. Surrealism. Resistance.